PENGATURAN DAN PENGAWASAN BANK SYARIAH - Siregar, Nur Khotia Harahap, Erpiana (Islamic Circle, 2021)
Sharia financial institutions were first established, namely Islamic banking in 1991. However, this financial institution has experienced good growth. Seeing the development of Islamic banks so far, which makes sharia principles the main foundation in running their business, it is necessary to have regulatory and supervisory institutions for Islamic banks in order to minimize the occurrence of fraud from various parties that can harm the wider community. The institution that regulated and supervised Islamic banks before 2014 was regulated and supervised by Bank Indonesia, then since 2014 it has been regulated and supervised by the OJK. In addition, Islamic banks are regulated and supervised by the DSN, which then represents the DPS in Islamic banking to supervise the activities of islamic banks in accordance with or not with syriah principles.